(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2024)
The establishment and upkeep of national health depends heavily on public health. The endeavor entails employing diverse tactics and measures to safeguard, enhance, and elevate the well-being of societies. Unani medicine, an ancient system of healing that originated in Greece and was later developed and enriched by Persian and Arabic physicians, has its own set of principles that can contribute to public health and the creation of a healthy nation.Unani fundamentals approaches health holistically, taking into account physical, mental, social and spiritual factors.In addition to providing customized care based on a patient’s constitution (temperament or Mizaj), Unani system of medicine has several other benefits for the general public’s health for example prevention and maintenance of one’s health through ‘Asbab Sitta Daruriyya waGhair Daruriyya’ that includes dietary recommendations, lifestyle modifications, sleep patterns and performing practices like cleanliness and moderation, doing exercise etc. Additionally, integrating Unani medicine into community health programs like health camps, awareness sessions and distribution of herbal formulations for common ailments can provide a holistic approach to healthcare. In summary, Unani medicine’s emphasis on holistic health, preventive care, individualized treatment, natural remedies, lifestyle modifications, community health, and integration with modern medicine aligns with the goals of public health. The objective of this study is to shed light on the foundations of Unani medicine, which is crucial for preserving health at all levels and enhancing it when combined with contemporary medical procedures to improve health both nationally and among individuals.